2009 IEEE International Memory Workshop 2009
DOI: 10.1109/imw.2009.5090575
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Fluorine Incorporated Band Engineered (BE) Tunnel (SiO2/ HfSiO/ SiO2) TANOS with Excellent Program/Erase & Endurance to 10^5 Cycles

Abstract: We demonstrate for the first time a fluorine incorporated bandengineered (BE) tunnel oxide (SiO 2 /HfSiO/SiO 2 ) TANOS with excellent program / erase (P/E) characteristics and endurance to 10 5 cycles. Incorporating fluorine in the tunnel dielectric improves Si/SiO 2 interface resulting in excellent endurance of nearly constant over 3V P/E window for at least 10 5 cycles. Fluorine also reduces interface state generation during retention by ~20%. Furthermore, Fluorine passivates bulk traps leading to as much as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…As shown in Fig. 1(b), the AlO sample without fluorine plasma treatment displays an Al 2p peak at 74.2 eV [10], indicating Al-O bond formation, while the Al 2p peak of the AlOF sample with fluorine plasma treatment was deconvoluted into two peaks, one located at 74.2 eV due to the Al-O bond, another one located at 75.8 eV due to the formation of Al-F bond. Moreover, it is observed that the peak intensity of the Al-O bonds is reduced after incorporation of fluorine, meaning that Al-F bonds replace some Al-O bonds.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…As shown in Fig. 1(b), the AlO sample without fluorine plasma treatment displays an Al 2p peak at 74.2 eV [10], indicating Al-O bond formation, while the Al 2p peak of the AlOF sample with fluorine plasma treatment was deconvoluted into two peaks, one located at 74.2 eV due to the Al-O bond, another one located at 75.8 eV due to the formation of Al-F bond. Moreover, it is observed that the peak intensity of the Al-O bonds is reduced after incorporation of fluorine, meaning that Al-F bonds replace some Al-O bonds.…”
Section: Resultsmentioning
confidence: 96%
“…To obtain a similar P/E memory window for both devices, shorter pulse time and smaller voltage is required for the AlOF sample, meaning that less stress is applied on the thin tunneling layer and the endurance characteristic is enhanced [14]. Moreover, during the PDA at 900 °C, some incorporated fluorine atoms diffuse in the bulk of the MONOS capacitor to reach the interface between the Si substrate and SiO 2 forming strong Si-F bonds, which can improve the interface quality, thus also leading to better endurance characteristic [10]. Figure 4 displays the retention properties of both samples tested at room temperature and the energy-band diagram of the AlOF sample under retention mode.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve tunnel oxide reliability, a fluorine incorporation technique was reported [44][45][46]. Incorporating fluorine in the tunnel dielectric improves the Si/SiO 2 interface, resulting in excellent endurance over a 3 V P/E window for at least 1E + 05 cycles because the fluorine passivates defects in the tunnel oxide stack.…”
Section: Tunnel Barrier Engineering (Tbe)mentioning
confidence: 99%
“…[3][4][5][6][7]10) In addition, it also suffers from poor retention due to the charge-trapped around the triangular corners. To compensate both the programming time and data retention of GAA-FG, in this work, the tunnel barrier engineering concept of variable oxide thickness (VARIOT) [11][12][13][14][15][16] as tunnel layer is utilized. It has been previously studied for charge-trapping 15,16) and even for hybrid floating [17][18][19] gate devices and its performances as tunnel oxide layer for 3D FG cell is yet to be unveiled.…”
Section: Introductionmentioning
confidence: 99%